Numerical and experimental analysis of body armor polymer penetration resistance against 7.62 mm bullet - Gebrewahid Asgedom; Kumlachew Yeneneh; Getu Tilahun; Besufekad Negash (Heliyon)
Advanced materials are crucial for enhancing soldier safety through improved personal body armor. In contrast to conventional Kevlar-epoxy composites, this study examines the ballistic performance of a unique ECO-UHMWPE (Ultra-High Molecular Weight Polyethylene) vest. The aim is to achieve a lightweight design with superior impact resistance, addressing limitations of the current armor used by the Ethiopian Defense Force. A comprehensive finite element analysis (FEA) was conducted using Abaqus explicit dynamics software to simulate the impact of 7.62 × 39 mm projectiles at various ranges (50m, 100m, 150m, and 200m). Material properties, laminate thickness, projectile velocity, and number of layers were systematically varied to assess their impact on vest performance. Results showed that ECO-UHMWPE vests exhibited significantly lower stress values and minimal deformation, particularly at close ranges with high projectile kinetic energy, outperforming Kevlar vests. Ballistic testing validated the FEA, with ECO-UHMWPE vests achieving a 22.44 % weight reduction (3.49 kg, 12 mm thick) compared to traditional Kevlar vests (4.5 kg, 15 mm thick) and offering a 30 % reduction in deformation and a 25 % increase in energy absorption. This analysis demonstrates the potential of ECO-UHMWPE for lighter, more effective body armor, paving the way for next-generation personal protective equipment.